Application of the Moora Method in Selection of the Best Teacher At SMK YAPIM Biru-Biru - Marpaung, Endra A.P (Marcha Institute, 2024)
The teacher has the main task of educating, teaching, guiding, directing, training, assessing and evaluating his students at school. Teachers are considered achievers because teachers have the ability to carry out their duties at school, are successful in carrying out assignments, have personalities that are in accordance with the teaching profession and have educational insights. A decision support system or Decision Support System (DSS) is a system that assists in making a decision in an organization or companies by applying methods that are appropriate to the areas of decision taken, manual decision making without the help of SPK will result in unobjective and imprecise assessments. The Moora method is a method for making decisions that have many criteria by applying weights to each criterion. The system created can help the school to determine aspects of assessment based on criteria according to the needs of the school so that it is more flexible.